2008
DOI: 10.1645/ge-1618.1
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distributions and Origins of Human Head Lice (Pediculus humanus capitis) Based on Mitochondrial Data

Abstract: Human head lice (Pediculus humanus capitis) are subdivided into 3 deeply divergent mitochondrial clades (Clades A, B, and C), each having unique geographical distributions. Determining the evolutionary history and geographic distribution of these mitochondrial clades can elucidate the evolutionary history of the lice as well as their human hosts. Previous data suggest that lice belonging to mitochondrial Clade B may have originated in North America or Asia; however, geographic sampling and sample sizes have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 30 publications
6
84
0
2
Order By: Relevance
“…h . humanus , are obligatory hematophagous parasite that thrived exclusively on human blood for thousands of years [1, 2]. The two lice are now usually considered members of a single species as opposed to separate species [3, 4], each louse lives and multiplies in a specific ecological niche: hair for head lice and clothing for body lice [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…h . humanus , are obligatory hematophagous parasite that thrived exclusively on human blood for thousands of years [1, 2]. The two lice are now usually considered members of a single species as opposed to separate species [3, 4], each louse lives and multiplies in a specific ecological niche: hair for head lice and clothing for body lice [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analysis of mitochondrial genes has permitted the classification of Pediculus humanus into three several clades or haplogroups, referred to as A, B, and C [1, 2, 7, 8, 9]. Haplogroup A is the most common, and possesses a global distribution, including both head and body lice [1, 2, 6, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on the COI and Cyt b genes demonstrated that body lice ( P. humanus corporis ) and head lice are separated into three clades, A, B, and C [6]. Head lice could be found in a relatively specific geographic distribution for each clade [7]. Clade A has worldwide distribution [8], clade B is found in Europe, Australia, North America, and Central America [9], and clade C is found in Nepal [10], Ethiopia [11], and Senegal [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of human Demodex species found genetic differences in the mitochondrial CO1 gene between mite populations that inhabit the eyelashes versus mite populations that inhabit the skin [20]. In addition, studies of another human-associated parasite, lice ( Pediculus humanus ), have found strong genetic structure between geographic lineages [4], [5], [21]. Geographic structure among human-associated Demodex lineages is expected, given that these mites are more intimately associated with the body than lice and seemingly less mobile, yet the minimal data that exist have not yet recovered such variation [22].…”
Section: Introductionmentioning
confidence: 99%